HOW AI TOOLS CAN SUPPORT ENGLISH WRITING DEVELOPMENT - Gulchehra Agzamxanova; Yaroslav Golovko (Bright Mind Publishing, 2025)
Artificial intelligence has become a valuable tool in education, particularly in improving English writing skills. This article explores how AI-powered tools support learners by providing grammar and spelling corrections, enhancing vocabulary, improving sentence structure, detecting plagiarism, and assisting with idea generation. AI tools offer real-time feedback and personalized learning experiences, making them highly effective in writing development. While AI can significantly enhance writing skills, it is essential for learners to balance its use with independent practice to develop their own critical thinking and creativity. The findings suggest that AI tools can serve as powerful writing assistants, but they should complement rather than replace human effort.
Keywords: Artificial intelligence, writing development, grammar correction, vocabulary, improve writing skill, creativity, critical thinking.